2018
DOI: 10.7196/samj.2018.v108i2.12601
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal and paediatric bloodstream infections: Pathogens, antimicrobial resistance patterns and prescribing practice at Khayelitsha District Hospital, Cape Town, South Africa

Abstract: Background. The epidemiology of neonatal and paediatric community-acquired and healthcare-associated bloodstream infections (BSI) at South African (SA) district hospitals is under-researched. Objective. Retrospective review of neonatal and paediatric BSI (0 -13 years) at Khayelitsha District Hospital, Cape Town, SA, over 3 years (1 March 2012 -28 February 2015. Methods. We used laboratory, hospital, patient and prescription data to determine BSI rates, blood culture yield and contamination rates, pathogen prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…and up to 30% ESBL-producing K. pneumoniae [143]. While most of the surveillance is generated from teaching hospitals a study comparing district and tertiary facilities in KwaZulu-Natal province demonstrated AMR increasing from the district level to the tertiary facility, but with those referred upward having higher rates than those treated only in the district facility, but both facilities had increased rates for the longer-stay patients (> 48 h) [144,145].…”
Section: A Snapshot Of Amr Surveillance Programs and The Epidemiologymentioning
confidence: 99%
“…and up to 30% ESBL-producing K. pneumoniae [143]. While most of the surveillance is generated from teaching hospitals a study comparing district and tertiary facilities in KwaZulu-Natal province demonstrated AMR increasing from the district level to the tertiary facility, but with those referred upward having higher rates than those treated only in the district facility, but both facilities had increased rates for the longer-stay patients (> 48 h) [144,145].…”
Section: A Snapshot Of Amr Surveillance Programs and The Epidemiologymentioning
confidence: 99%
“…Studies suggest that bacteremia in hospitalized African children exceeds that of high-income countries and that gram-negative organisms, in particular non-typhoidal Salmonella (NTS), are among the most common isolates, especially where the prevalence of HIV and malaria is high (Reddy et al, 2010;Feasey et al, 2012;Mandomando et al, 2009). Other common causes of reported bacteremia in HIVinfected children have included Streptococcus Pneumonia, Staphylococcus Aureus and Enterbacteriaceae (Crichton et al, 2018;Hill et al, 2007). Existing estimates as to the burden of most pathogenic bacterial infections in sub-Saharan Africa is predominantly limited to urban areas, thus the impact of bacteremia in children under-five years of age is largely unknown, as many people live in rural areas (Reddy et al, 2010;Berkley et al, 2005;Sigaúque et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Bacteremia is a major cause of morbidity and mortality worldwide, with a high disease burden in developing countries and among children under 5 years old ( Crichton et al, 2018 ). Children infected with HIV present with patterns of bacteremia that are different in severity and frequency and are generally associated with poor prognosis ( Jaspen et al, 2008 ; Kolo et al, 2015 ; Musiime et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…1 Although candidemia accounts for 0.6%-6% of all pediatric bloodstream infections in South Africa, the incidence in children is rarely reported. 9,10 There has also been a shift in the Candida species causing candidemia globally, although the dominant species varies by region. 1,11 Single-and multicenter studies in South Africa have shown a shift from Candida albicans to Candida parapsilosis as the major cause of candidemia.…”
mentioning
confidence: 99%
“…1 Although candidemia accounts for 0.6%–6% of all pediatric bloodstream infections in South Africa, the incidence in children is rarely reported. 9,10…”
mentioning
confidence: 99%